The identification of Teachers Difficulties in Designing of Learning Materials Based on STEM at Central Aceh Senior High School - Indrawan, Deni Fahlawi; Syukri, M; Halim, Abdul (Universitas Syiah Kuala, 2020)
The problem in this research is what components are the difficulties for high school physics teachers at Central Aceh in designing STEM-based learning tools? This study aims to determine the difficulties of high school physics teachers in Central Aceh in designing STEM-based learning tools. The approach used in this research is a quantitative approach and descriptive type. The subjects of this study were all high school physics teachers in Central Aceh. Data collection was carried out by means of a questionnaire. The questionnaire data was processed with a descriptive percentage. The conclusion in this study is that the difficulty level of teachers is the highest in designing STEM-based learning tools on the Pedagogical Content Knowledge (PCK) component as many as 18,20 % of teachers, on the Content Knowledge (CK) component as many as 15,15 % of teachers and on the Technological Content Knowledge (TCK) component as many as 14,05 % of teachers. It is recommended for teachers to master mathematics/science in order to equip teachers knowledge in designing classroom learning tools and mastering technology to determine student needs in learning such as Twitter, blog, Facebook to support the teaching and learning process.